A Valuable Source for the Study of a Right-wing Guerrilla: The Cadernos de Gorongosa of Renamo (1983-1985) - (:unkn) unknown (My University, 2021)
On August 28, 1985, the headquarters of the “anti-Marxist” Mozambican guerrilla group (Resistência Nacional de Moçambique, Renamo) was stormed by Zimbabwean and Mozambican government forces. Renamo was able to evacuate the base but lost part of its archives, including what later became known as the Cadernos de Gorongosa (i.e. the Gorongosa Notebooks). The Mozambican government security services were quick to study them to prove that, despite the Nkomati Accords (1984), South Africa kept on supporting the Mozambican rebellion. The author was able to work through some of these Cadernos, consisting of thousands of handwritten messages—these were decoded transcripts of communications between the commander-in-chief and regional and local guerrilla groups. This makes it possible to study the daily life of this “right-wing guerrilla.” The article reproduces some of these messages, which are now available for consultation in Lisbon.
Keywords: African Research